Precise single column resection and reconstruction with femoral head plus total hip replacement for primary malignant peri-acetabulum tumors - Yongkun Yang; Yuan Li; Weifeng Liu; Xiaohui Niu (Scientific Reports, 2024)
Abstract To evaluate whether single acetabular column can be reserved and the effect of reconstruction with femoral head plus total hip replacement (THR) for primary malignant peri-acetabulum tumors. From 2007 to 2015, nineteen patients with primary malignant peri-acetabulum tumors were enrolled. All cases underwent single column resection with clear surgical margins. Ten of the 19 tumor’s resections were assisted by computer navigation. Femoral heads were applied to reconstruct anterior or posterior column defects; THR was used for joint reconstruction. The surgical safety, oncologic outcome and prosthesis survivorship and function were evaluated by regular follow-up. The average follow-up period was 65.9 months. Surgical margins contained wide resection in 12 cases and marginal resection in 7 cases. One patient with Ewing's sarcoma died 14 months postoperative due to lung metastasis. One case with chondrosarcoma had recurrence. One prosthesis was removed due to infection. The average MusculoSkeletal Tumor Society (MSTS) function score was 83.7%. Due to the relative small number of cases, there was no significant difference in the recurrence rate and prosthesis failure rate between the navigation group and non-navigation group. Single column resection and reconstruction with femoral head autograft plus THR is an effective, safe method with less complication rate and better functional outcome for patients with peri-acetabular tumors.